Leading factors to lack usage of printed dictionaries in searching vocabularies among students in the department of Arabic language and literature in International Islamic University Malaysia - Radhwa Abu Bakar,; Siti Norbayani Ngamar, (Penerbit Universiti Kebangsaan Malaysia, 2022)

(untitled)
This research aims to find out the factors that lead to the lack usage of printed dictionaries in searching the meanings of Arabic vocabulary, and to reveal the means used by students in the Department of Arabic Language and Literature at the International Islamic University in Malaysia, while identifying their preferred method for searching the meanings of those vocabulary.This research adopted a quantitative approach by distributing a questionnaire to students in the third and fourth year at the Department of Arabic Language and Literature at the International Islamic University in Malaysia. The study found that there are four factors that lead to the lack usage of printed dictionaries in searching the meanings of Arabic vocabulary, which are; psychological factors, financial factors, external factors and the dictionary factors. The biggest factor is the dictionary factors itself. As for the means used by these students in searching the meanings of Arabic vocabulary, they are using electronic dictionaries of monolingual (Arabic-Arabic), bilingual (Arabic-other languages), Google Translate, and using smart phones. As for the the preferable method used by the students in searching the meanings of the vocabularies, is utilizing available electronic dictionaries via smart phones.